Changes in practice and perception of hepatitis C and liver transplantation: Results of a national survey. Issue 6 (21st September 2018) - Shaffer, Ashton A.; Thomas, Alvin G.; Bowring, Mary Grace; Van Pilsum Rasmussen, Sarah E.; Cash, Ayla; Kucirka, Lauren M.; Alqahtani, Saleh A.; Gurakar, Ahmet; Sulkowski, Mark S.; Cameron, Andrew M.; Segev, Dorry L.; Durand, Christine M.
Abstract: With new practice guidelines, it is important to understand how liver transplant (LT) centers have incorporated direct‐acting antivirals (DAAs) into the management of hepatitis C virus‐infected (HCV+) candidates and recipients. To explore how DAAs have affected LT centers' willingness to treat HCV+ candidates and recipients and to use HCV+ donors, we surveyed high volume US LT centers (11/2014‐12/2015) regarding practices for HCV+ candidates, recipients, and donors, before vs after DAAs. We used the Scientific Registry of Transplant Recipients to compare centers' number of LTs, HCV+ recipients, and HCV+ donors in the years before (1/1/2012‐12/31/2013) and after (1/1/2016‐12/31/2017) survey administration. Of 80 centers contacted, 57 (71.3%) responded, representing 69.0% of the total volume of LTs in 2013. After DAAs, most centers increased treating candidates with low (≤15) model for end‐stage liver disease (MELD) (85.2%), intermediate/high (>15) MELD (92.6%), and hepatocellular carcinoma (79.6%). There was consensus to treat low MELD candidates (90.8% "most of the time/always"), but less certainty for intermediate/high MELD candidates (48.2% "sometimes"). Universal post‐LT HCV treatment increased (7.4% vs 57.4%). After DAAs, 42.6% were more willing to use HCV+ donors for HCV+ candidates, and 38.9% were willing to consider using HCV+ donors for HCV− candidates. Overall, with DAAs, centers were more willing to treat HCV+ candidates and recipients and to use HCV+ donors; recent recommendations may help to guide treatment decisions for intermediate/high MELD candidates.